EDUKASI KESEHATAN SEBAGAI UPAYA MENINGKATKAN PENGETAHUAN ORANG TUA TENTANG CAMPAK PADA ANAK DI RSUD RADEN MATTAHER JAMBI - Rina Oktaria; Fadliyana Ekawaty; Suryati Suryati; Diana Evasari; Yusnilawati Yusnilawati; Suryadi Imran (Jurnal Pengabdian Masyarakat, 2026)
Measles is an acute infectious disease that remains a health problem in children due to its high transmission rate and potential to cause serious complications. Parents’ lack of knowledge regarding the signs and symptoms, transmission, prevention, and importance of measles immunization is one of the factors that increases the risk of measles in children. Health education is one of the efforts that can be carried out to improve parents’ knowledge about measles in children. This community service activity aimed to improve parents’ knowledge about measles in children through health education in the pediatric ward of RSUD Raden Mattaher Jambi. The activity was conducted on April 7, 2026, involving 15 parents of pediatric measles patients. The methods used included health education through lectures, discussions, question-and-answer sessions, as well as the distribution of leaflets and PowerPoint media. Knowledge levels were measured before and after the education session using questionnaires through pretest and posttest methods. The results showed that before the education session, most respondents had poor knowledge levels, namely 7 people (46.7%), moderate knowledge levels were 5 people (33.3%), and good knowledge levels were 3 people (20%). After the health education was provided, there was an increase in knowledge, where most respondents had good knowledge levels, namely 12 people (80%), and moderate knowledge levels were 3 people (20%). Health education activities were proven effective in improving parents’ knowledge about measles in children. It is expected that health education activities can be carried out continuously as promotive and preventive efforts to improve children’s health.